(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
The article analyzes the current state of the transport infrastructure of the Republic of Karakalpakstan, identifies key problems of its development in the context of the transition to a modern market economy. The areas of state and regional support aimed at forming an effective transport network that contributes to increasing the competitiveness of the region are considered.